Evolution of macro and micromorphology of Eriocaulon (Eriocaulaceae) and its relation with the aquatic environment - Oliveira, A. L. R; Baleeiro, P. C.; Darshetkar, A. M.; Choudhary, R. K. (Rheedea, 2025)
Eriocaulon L. is a pantropical genus comprising approximately 495 species. Previous taxonomic studies have proposed infrageneric classifications based on selected morphological characters; however, molecular phylogenetic analyses have shown that most of these classifications are paraphyletic. A recent multivariate analysis of anatomical data identified two major groups within the genus: one composed of amphibious species and the other of aquatic species. In this context, the present study aims to test the hypothesis that these groups correspond to distinct evolutionary clades by conducting a cladistic analysis of Eriocaulon based on morphological data. Our analysis included 65 species of Eriocaulon and seven outgroup species, using a dataset of 89 macro- and micromorphological characters. Parsimony analyses conducted in TNT recovered 24 equally parsimonious trees. In all analyses, Eriocaulon was resolved into two main clades. One clade comprises amphibious species from Africa and the Americas and shares plesiomorphic character states with Mesanthemum Körn., including palisade epidermal cells, stomatal chambers, and numerous vascular bundles in the leaf. The other clade, comprising aquatic species distributed across all continents, is characterized by derived character states, including a reduced number of vascular bundles, isodiametric epidermal cells, and the loss of stomatal chambers. These results suggest that the evolutionary history of Eriocaulon is closely tied to anatomical adaptations that facilitate colonization of aquatic environments.